Pengaruh gaya kepemimpinan kepala sekolah terhadap kinerja guru bimbingan dan konseling di SMA negeri Jakarta Timur - Yulinda Siregar (TERAPUTIK: Jurnal Bimbingan dan Konseling, 2018)
School counselor didn’t show a significant work. This is based on loss of ability, lack of skills acquired by counselors in addressing the learners. On the other hand, the headmaster's style of command also contributes to the counselor's style of work in school. This study aims to determine the influence of principal leadership style on counselor performance in high school. The unit of analysis in this study is a counselor who amounted to 73 people and served in high school throughout East Jakarta. Result of this study indicates that there is an influence on the performance leadership of Principal counselor.